A rare case report of bilateral synchronous carcinoma breast - Shah, Bhushan Anil; Yadav, Nagendra; Akhil, Kandarpa; Alam, Firoz (International Surgery Journal, 2017)
Bilateral Breast Carcinoma (BBC) is a rare entity with incidence of synchronous carcinoma being 2-5% of all breast malignancies, which is much less than metachronous carcinoma. Synchronicity/metachronicity are usually associated with local and lymphatic spread and with blood-borne spread to lungs, bones and liver. Moreover, BBC are mostly lobular carcinomas but we report a rare case of Infiltrating Ductal Carcinoma (IDC), medullary type as the primary carcinoma. 56-year-old female who presented with a lump in her right breast for 6 months and lump in her left axilla. There was no e/o palpable lump in her left breast. Trucut biopsy was taken from both the lumps and was s/o infiltrating ductal carcinoma. Different histological subtypes with different grades of tumour in both breasts suggested synchronous primary tumours. Early detection of the contralateral tumour is of utmost importance emphasizing the significance of breast self-examination. Screening tools like MRI have a greater sensitivity compared to Mammography. There are no clear treatment guidelines for bilateral breast cancer. Patients are often treated with bilateral mastectomy, with breast conservative surgery having unclear importance. Meticulous diagnosis and appropriate management help to improve the longevity with an improved quality of life.